Zophobas morio larvae as a novel model for the study of Acinetobacter virulence and antimicrobial resistance - Rakovitsky, Nadya; Temkin, Elizabeth; Hameir, Amichay; Lurie-Weinberger, Mor; Keren-Paz, Alona; Carmeli, Yehuda (Frontiers in Microbiology, 2024)
Mammalian models for in vivo testing of bacterial virulence raise ethical issues and are expensive and time consuming. As an alternative, non-mammalian models are sought. Galleria mellonella larvae have been used as a model to study of several bacterial pathogens. However, their maintenance is challenging and commercial supply is low. Here, we aimed to establish the Zophobas morio larvae as an alternative non-mammalian model for evaluation of pathogenicity and antimicrobial susceptibility of Acinetobacter baumannii. We infected Z. morio with Acinetobacter strains and determined optimal temperature and inoculum. To visualize the bacterial distribution within the larvae, H&E (hematoxylin and eosin) stain was performed.Next, survival model of infected larvae was established and virulence compared between strains. The effect antimicrobial treatment in relation to antibiotic susceptibility was studied.Our results demonstrate that Z. morio can be used as a model system for in vivo studies of A.